Unveiling the Illicit Trade: Legal Perspectives on Lobster Seed Smuggling in Batam City - Shahrullah, Rina Shahriyani; Ong’eta, Wyclife; Nurlaily, Nurlaily; Santoso, Topo; Zin, Hakimah Muhammad; Ramadhani, Mochamad Rizki (Universitas Negeri Semarang, 2025)
Despite the recent government legal updates, lobster seed smuggling remains a lucrative business in Batam City. This study aims to analyze the linkage of international and national laws with Batam City's efforts in combating lobster seed smuggling. It also examines the roles and challenges faced by the stakeholders in Batam City in tackling this issue. Utilizing empirical legal research and socio-legal approaches, the study relied on both secondary and primary data, incorporating literature studies and interviews with the Criminal Investigation Unit of Barelang City Police and the Batam Fish Quarantine Station. Qualitative analysis, guided by Mochtar Kusumaatmadja's Development Law Theory found that the Minister of Maritime Affairs and Fisheries Regulation No. 7 of 2024 has not stopped lobster seed smuggling via sea from Batam City to neighboring countries. It is concluded that this smuggling has an international dimension; consequently, CITES, UNCLOS, and UNTOC can serve to address the relationship between international law and local issues. Stakeholders in Batam City have implemented efforts by collaborating with stakeholders at the local, national, and international levels. Yet, they still encounter challenges, including educating the public. In response to these challenges, the best practices from Hong Kong, Australia, and Vietnam can be adopted by stakeholders in Batam City. They could also serve as references for other regions in Indonesia facing similar challenges. It is also concluded that Batam City's efforts to combat lobster seed smuggling offers key lessons, highlighting the need for legal reforms and broad collaboration involving the local community at all levels.